2016
DOI: 10.1128/jvi.02653-15
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Common Marmosets with GB Virus B Chimeric Virus Encoding the Major Nonstructural Proteins NS2 to NS4A of Hepatitis C Virus

Abstract: A lack of immunocompetent-small-primate models has been an obstacle for developing hepatitis C virus (HCV) vaccines and affordable antiviral drugs. In this study, HCV/GB virus B (GBV-B) chimeric virus carrying the major nonstructural proteins NS2 to NS4A (HCV NS2 to -4A chimera) was produced and used to infect common marmosets, since HCV NS2 to NS4A proteins are critical proteases and major antigens. Seven marmosets were inoculated intrahepatically with HCV NS2 to -4A chimera RNA for primary infection or intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Recently, Zhu et al . described a marmoset model infected with GBV‐B chimeric virus which supported consistent expression of six major HCV antigens including NS2 to NS4A. This novel small primate model was immunocompetent, providing an alternative model for antiviral drugs evaluation.…”
Section: Development Of Models For the Study Of Hcvmentioning
confidence: 99%
“…Recently, Zhu et al . described a marmoset model infected with GBV‐B chimeric virus which supported consistent expression of six major HCV antigens including NS2 to NS4A. This novel small primate model was immunocompetent, providing an alternative model for antiviral drugs evaluation.…”
Section: Development Of Models For the Study Of Hcvmentioning
confidence: 99%
“…It was further demonstrated that serum from these viremic animals caused infection and hepatic inflammation in naïve marmosets; however, viremia was intermittent, which appeared to correlate with the induction of cellular and humoral immune responses. A GBV-B/HCV chimera carrying HCV NS2 to NS4A caused viremia in marmosets for 20 weeks, and viremia was maintained even longer under immunosuppression [109]. These results from infection studies with GBV-B/HCV chimeras remain to be validated in larger cohorts of animals, to more accurately characterize their replicative capacities, correlates of immunological protection, and virally induced pathogenesis.…”
Section: Primate Virusesmentioning
confidence: 99%
“…A modest antibody response to HCV core and E2 proteins was also detected [ 81 ]. Marmosets infected with another HCV/GB-V chimeric virus expressing nonstructural proteins NS2 to NS4A of HSC also exhibited viremia with characteristics typical of viral hepatitis [ 82 ]. These findings indicated that common marmosets infected with chimeric viruses are valuable tools in the development of vaccines and antiviral drugs against HCV infection.…”
Section: Callithrix Jacchus Models Of Human LIVmentioning
confidence: 99%